Corporate Governance: A Case Study of Textile Industry of Punjab - Nachaal, Ruchika (Indian Journal of Finance, 2008)
The textile industry is the dynamic, growth oriented industry with strong technological bases The Indian textile industry enjoys major strengths in the global market. It is largely self-sufficient as regards as raw material, with India’s cotton crop being the third largest in the world. India has achieved self sufficiency in synthetic raw material as well as mainstream products like polyester staple fiber, polyester filament yarn, and acrylic fiber and viscose fiber though certain specialty polyester fiber and yarn are still improved. Substantial growth in the domestic market and tremendous upswing in the international and domestic market, as a result if free market access facilitated by GATT, spells a bright scenario for Indian Textile industry. New opportunities are emerging in downstream products like processed fabrics and finished and branded knit and woven garments with improvement in communications and electronic data transfer.